The making of the modern Philippines : pieces of a jigsaw state - Bowring, Philip (New York : Bloomsbury Academic, 2022)
"With a fractured geography and complex identity, The Philippines is an eclectic and unique mix of culture, environment, people and politics. Known mostly for natural disasters, migrant labour and dictatorial presidents, in this book Philip Bowing shows how it is much, much more. Deftly navigating the history of this populous island republic, The Making of the Modern Philippines traces its history to define and explain its position in the modern world. Looking past the headlines of volcanoes, earthquakes and violence, it asks why has the Filipino economy lagged behind its neighbours, explores the importance of its location in geopolitics, and investigates how its deep-rooted Catholicism clashes with the Islamic consciousness of the region in which it sits. Taking the history of the Philippines from its pre-colonial era, through its Spanish and American occupations and up to the modern day, it unravels the complex politics, culture, peoples and economy of this rich and unique nation. Engaging with challenges the Filipino people face today such as federalism, revolution, Mindanao, the diaspora, capitalism and relations with China, it rediscovers the struggles, culture and history of its past to understand the present"--
Fractured geography, complex identity -- More church than state -- 'Uncle Sam's brown boys' -- Choices of evils -- Old wine in new bottles -- Marcos: power corrupts absolutely -- Ladders and snakes -- Straight paths and road blocks -- Man with a gun -- 'Imperial' -- Manila's weak grip -- Lost advantage -- The root of poverty -- An unempowered economy -- Beyond the Bayan -- Of 'free trade' and the short arm of the law -- Happy families of conglomerate capitalism -- Mindanao: beckoning frontier -- Moros, datus, military and more -- Religion on its sleeve -- Left field lies fallow -- Foreign policy: all at sea.
Includes bibliographic references and index
Keywords: PHILIPPINES; MANNERS AND CUSTOMS; POLITICS AND GOVERNMENT; SOCIAL CONDITIONS; ECONOMIC HISTORY